REAL-TIME IMAGE PROCESSING FOR FLUOROSCOPIC IMAGING (2016)
A method for display of a fluoroscopic image sequence during ongoing image acquisition acquires and renders a first image of a subject on a display according to a first parameter setting, modifies the first parameter setting according to an operator instruction entered following acquisition of the first image, and applies the modified first parameter setting for acquiring and rendering one or more subsequent fluoroscopic images of the subject in the fluoroscopic image sequence.